Ações formativas com Tradutores e Intérpretes de Libras para o aperfeiçoamento das práticas interpretativas - Girke, Ityara Aguiar da Silva Pinto (Universidade Federal de São Carlos, 2024)
The rise of Sign Language Translators and Interpreters (also known as SLTI) in Brazil has been perceived in a myriad of spheres within society. These include mainstream education, from Elementary to High School years, in various community environments where mediation for communication between deaf and hearing people are necessary, as well as in most social media platforms. Nevertheless, it is perceivable that there are still gaps in interpretations which could be due to the lack of training of these professionals (Giamlourenço, 2018). Even with years of working in the field, most interpreters do not consider themselves competent to face the daily challenges in the educational sphere where the demand for this ype of professional has increased (Santos, 2014). Therefore, given the growing number of deaf students enrolled in schools, the need to train these educational interpreters (EI’s) has escalated. Thus, it is vital for them to be professionally qualified and feel confident to perform the role of mediator in order to positively contribute to deaf students’ learning journey (Santos, 2021). For this reason, the primary aim of this research is to investigate the effectiveness of mediated formative practices for the development of EIs' practices. The specific objectives include organizing a continuing education course for SLTI’s working at one of the campuses of the Federal Institute of São Paulo (participants), from a mediated perspective, to investigate whether reflection on practicing is effective in developing interpretive skills. The study was conducted using a qualitative, exploratory approach, through action research, offering a continuing education course for the participants, following the theoretical principles of Vygotsky ([1926] 2001; [1934] 1998; [1930] 1984; [1930] 2004). The training took place remotely. The sessions were recorded, and based on the collected data, an evaluation was made to determine which aspects of the training - based on mediation and reflection on practice - were most effective in developing these interpretive skills. The aim is to contribute to the field of training sign language translators and interpreters so they can carry out their work, enhancing the quality of deaf education.
Training actions with Libras Translators and Interpreters to improve interpretive practices
Keywords: Tradutores e intérpretes educacionais; Mediação; Reflexão; Relações; Educational translators and interpreters; Mediation; Reflection; Relationships; CIENCIAS HUMANAS